2009
DOI: 10.12968/ijpn.2009.15.4.41967
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the literature surrounding the transition into palliative care: a scoping review

Abstract: This article explores the current literature surrounding transitions into palliative care. Transitions in care have become more frequent and complex in the Canadian healthcare system. Plagued with difficulty, fear and misunderstanding, the transition into palliative care is one of the most confusing and traumatic transitions a patient and family can face. Despite this, however, transitions into palliative care have been commonly overlooked in transitional research. A scoping review of the existing literature o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 15 publications
1
48
0
4
Order By: Relevance
“…13,18 Understanding how a patient-caregiver dyad experiences this transition can help clinicians develop greater capacity to support them during this meaningful but difficult time period. Enhanced clinician understanding also can limit unwanted aggressive care and contribute to adaptation in bereavement.…”
Section: Introductionmentioning
confidence: 99%
“…13,18 Understanding how a patient-caregiver dyad experiences this transition can help clinicians develop greater capacity to support them during this meaningful but difficult time period. Enhanced clinician understanding also can limit unwanted aggressive care and contribute to adaptation in bereavement.…”
Section: Introductionmentioning
confidence: 99%
“…53 A phased transition or simultaneous care approach recognises that treatment goals evolve and that concurrent curative and palliative care may be most appropriate. 25 A scoping review by Marsella 54 identified three key elements that complicate the transition to palliative care. First is the nature of the transition and what it means to patients.…”
Section: Introductionmentioning
confidence: 99%
“…Duhamel & Dupuis [45] argued that family members may not believe that the patient is terminally ill because they do not believe that they have the capacity to deal with such an eventuality. Transition to palliative day-care can be a difficult time for both the patient and caregiver provoking significant worries for both groups and often the transition causes a realisation that a loved one may not be cured from their illness [46]. Within this study the transition into palliative day-care was more than a physical process and represented the individual's passage from one set of hope to another [47].…”
Section: Discussionmentioning
confidence: 98%